Effect of Digoxin Therapy on Mortality in Patients With Atrial Fibrillation: An Updated Meta-Analysis - Wang, Xiaoxu; Luo, Yi; Xu, Dan; Zhao, Kun (Frontiers in Cardiovascular Medicine, 2021)
Background: Whether digoxin is associated with increased mortality in atrial fibrillation (AF) remains controversial. We aimed to assess the risk of mortality and clinical effects of digoxin use in patients with AF. Methods: PubMed, Embase, and the Cochrane library were systematically searched to identify eligible studies comparing all-cause mortality of patients with AF taking digoxin with those not taking digoxin, and the length of follow-up was at least 6 months. Hazard ratios (HRs) with 95% confidence intervals (CIs) were extracted and pooled. Results: A total of 29 studies with 621,478 patients were included. Digoxin use was associated with an increased risk of all-cause mortality in all patients with AF (HR 1.17, 95% CI 1.13–1.22, P < 0.001), especially in patients without HF (HR 1.28, 95% CI 1.11–1.47, P < 0.001). There was no significant association between digoxin and mortality in patients with AF and HF (HR 1.06, 95% CI 0.99–1.14, P = 0.110). In all patients with AF, regardless of concomitant HF, digoxin use was associated with an increased risk of sudden cardiac death (SCD) (HR 1.40, 95% CI 1.23–1.60, P < 0.001) and cardiovascular (CV) mortality (HR 1.27, 95% CI 1.08–1.50, P < 0.001), and digoxin use had no significant association with all-cause hospitalization (HR 1.13, 95% CI 0.92–1.39, P = 0.230). Conclusion: We conclude that digoxin use is associated with an increased risk of all-cause mortality, CV mortality, and SCD, and it does not reduce readmission for AF, regardless of concomitant HF. Digoxin may have a neutral effect on all-cause mortality in patients with AF with concomitant HF. Systematic Review Registration:https://www.crd.york.ac.ukPROSPERO.